Ogórki małosolne antropomorfizowane. Próby o wierszu Za szkłem - Adam Poprawa (Przestrzenie Teorii)
The last volume of poetry by Stanisław Barańczak, titled Chirurgiczna precyzja (Surgical precision) features the poem Za szkłem (Behind glass). It is an extremely ironic and ambiguous work. The interpretation provided in this paper points to the exceptional importance of this text for Barańczak’s poetry as a whole.